Partly cloudy ethics in war, espionage, covert action, and interrogation - Perry, David L. 1959 (Rowman & Littlefield, 2016)
"Partly Cloudy : Ethics in War, Espionage, Covert Action, and Interrogation explores a number of wrenching ethical issues and challenges faced by military and intelligence personnel. It provides a robust and practical approach to analyzing ethical issues in war and intelligence operations, and applies careful reasoning to issues of vital importance today, not only for soldiers, intelligence professionals, and policy makers, but also for the citizens they serve and protect. This new edition has been updated throughout and includes new contents, to deal with critical issues such as torturing detainees, using espionage to penetrate terrorist cells, mounting covert actions to undermine hostile regimes, practicing euthanasia on the battlefield as mercy-killing, or using targeted killings as a means to fight insurgencies"--Provided by publisher